Impact of poxB, pta, and ackA genes on mineral‐weathering of Enterobacter cloacae S71. (7th May 2018) - Wang, Qi; Zhang, Zhendong; Zhu, Ying; He, Linyan; Sheng, Xiafang
Abstract : In this study, biotite weathering behaviors were compared between mineral‐weathering bacteria Enterobacter cloacae S71, mutant strains created by the deletion of poxB, pta, and ackA genes involved in acetate formation, and their complemented strains. Compared to strain S71, a decrease in bacterial growth was observed during the early and middle stages for the mutant Δ poxB and at the middle and later stages for the mutants Δ pta and Δ ackA . Dissolved Al and Fe concentrations were lower during the early stage for strain Δ poxB, at the early or middle stage for strain Δ pta, and at the middle and later stages and throughout the weathering process for strain Δ ackA, compared to strain S71. Acetate production was depressed during the early stage for strain Δ poxB, at the early and middle stages for strain Δ pta, and throughout the weathering process for strain Δ ackA . Overall, the ackA gene exhibited a larger impact on dissolved Fe and acetate concentrations than both the poxB and pta genes. Reduced bacterial growth and lower dissolved Al, Fe, and acetate concentrations recovered by the complemented strains. These results show that strain S71 promoted mineral weathering through the production of acetic acid with distinctive impacts by the genes involved in acetate.